1988
DOI: 10.3109/08910608809140185
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the Gingival Pocket by Enrichment of Subgingival Microflora in Human Serum in Chemostats

Abstract: This study was undertaken to design a relevant model system with conditions resembling the gingival pocket, in order to identify ecological factors that stimulate the establishment and maintenance of pathogenic subgingival microflora. Human serum as a substitute for gingival exudate was used in continuous culture enrichments of subgingival plaque to enable the selection of slow-growing (D gO.08 h-I ) consortia of microorganisms. After one week of continuous cultivation, species such as Treponema denticola, Pep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

1989
1989
1997
1997

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(35 citation statements)
references
References 34 publications
2
32
0
Order By: Relevance
“…The collective evidence from numerous in vitro and in vivo studies has demonstrated that the persistence and diversity of the resident oral microflora are due to the endogenous nutrients provided by the host (Littleton et al, 1967;van der Hoeven, 1982a,b, 1984;Beighton and Hay day, 1986). In particular, salivary mucins (glycoproteins) act as the main source of carbohydrates for plaque bacteria, and the degradation of the oligosaccharide side-chains depends on the concerted action of consortia of different species, each with complementary profiles of glycosidase activity ter Steeg et al, 1988;van der Hoeven and Camp, 1991;. Furthermore, the growth of some species can be dependent on the provision of nutrients by other oral bacteria.…”
Section: Nutrientsmentioning
confidence: 99%
See 2 more Smart Citations
“…The collective evidence from numerous in vitro and in vivo studies has demonstrated that the persistence and diversity of the resident oral microflora are due to the endogenous nutrients provided by the host (Littleton et al, 1967;van der Hoeven, 1982a,b, 1984;Beighton and Hay day, 1986). In particular, salivary mucins (glycoproteins) act as the main source of carbohydrates for plaque bacteria, and the degradation of the oligosaccharide side-chains depends on the concerted action of consortia of different species, each with complementary profiles of glycosidase activity ter Steeg et al, 1988;van der Hoeven and Camp, 1991;. Furthermore, the growth of some species can be dependent on the provision of nutrients by other oral bacteria.…”
Section: Nutrientsmentioning
confidence: 99%
“…For example, black-pigmented anaerobes require hemin for growth, and they probably obtain this key cofactor by degrading heme-containing host molecules (hemoglobin, hemopexin, haptoglobin) present in GCF, the flow of which is increased during inflammation. The detection and levels of periodontal pathogens were enhanced when enrichment cultures of subgingival plaque were carried out on human serum, which was used to simulate growth on GCF (ter Steeg et al, 1987Steeg et al, , 1988. There are also (contradictory) data implying that the rise in subgingival levels of Prevotella intermedia seen sometimes during pregnancy is due to the metabolism of the hormones estradiol and progesterone (Kornman, 1982), which can be detected in GCF, while increases in Prevotella spp.…”
Section: Nutrientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, virulence factors such as hyaluronidase have been identified in this species.23 It may be of interest, that in the continuous culture enrichments in human serum, an inverse relation seemed to exist between P . micros and T, denticola, 20 suggesting that the substrates of their niches may show some overlapping.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, continuous cultures, in contrast to batch cultures, offer the possibility to study mixed populations of microorganisms. Accordingly, mixed continuous cultures have been used as a model for oral microfloras (4,19).…”
mentioning
confidence: 99%